Comparing spatial perception/cognition in real versus immersive virtual environments - it doesn't compare! - Riecke, B. E; Moura, D. (50th Annual Meeting of the Psychonomic Society (Psychonomics), 2009)
Virtual reality (VR) is increasingly used in psychological research and applications, but does VR really afford natural human spatial perception/cognition, which is a prerequisite for effective spatial behavior? Using judgment of relative direction (JRD) tasks, Riecke and McNamara (2007, Abstracts of the Psychonomic Society) demonstrated orientation-specific interference between participant's actual orientation in an empty rectangular room and their to-be-imagined orientation in a previously learned room. To test whether VR yields similar interference, we replicated their study using a modified condition: We used an empty virtual (instead of real) test room presented on a 180x150deg video projection. After learning 15 target objects in a rectangular office, participants performed JRD tasks ("imagine facing X, point to Y") while facing different orientations in the virtual test room. Despite using identical procedures, seeing the virtualenvironment did not produce the same interference as a comparable real-world stimulus, suggesting qualitative differences in human spatial perception/cognition in real versus computer-simulated worlds.
Keywords: Riecke; Riecke_2009; bernhard-riecke; egocentric; frame; framework; iSpaceWeb; iat812; interference; model; orientation; posterWithoutPaper; proj--Moura2009-JRDInVR; reference; spatial; spatial-cogn-vr-rw; talkWithoutPaper; theory; updating